An experimental study on the dynamic response of a hull girder subjected to near field underwater explosion. (December 2015) - Zhang, Zhenhua; Wang, Yuanxin; Zhao, Haifeng; Qian, Haifeng; Mou, Jinlei
Abstract: An experiment of hull girder model subjected to near field underwater explosion at midship is implemented. High-speed photography is applied to achieve the time history of hog displacement of the hull girder model subjected to shock wave of undex. The determination method of hog distortion using these show-motion pictures is presented. The experiment also achieves the local plate distortion of the hull girder model. Based on these works, the damage mechanism and mode of hull girder subjected to near field undex at midship are discovered. Finally, the coupling effect between whole motion of hull girder and distortion of local structure is discussed. Highlights: High speed images of ship model subjected to near field undex is achieved. Final plastic overall deformation of hull girder subjected to undex is presented. Final plastic local deformation of amidships bottom plate is presented. The time history of moment of inertia of amidships cross section appears two linear parts approximately. Overall deformation and movement of hull girder have great effect on local deformation.